Physical self-concept in a sample of primary students and its relationship with gender and out of school sport practice - Bernardino Javier Sánchez-Alcaraz Martínez; Alberto Gómez-Mármol (Federación Extremeña de Balonmano; University of Extremadura, 2014)
The aims of this article are to evaluate the physical self-concept in adolescence and to get to know the outcomes in the different dimensions in the physical self-concept and to check the influence of the variables gender and level of physical activity. 125 students in Primary Education took part, aged between 11 and 13 years, and answered the Children Physical Self Questionnaire. Results in relation to gender indicated that boys had higher levels of self-perceived competence (p=.003), physical appearance (p=.000) and self-confidence (p=.029). With regard to sport practice, those participants who practice sports habitually obtain higher values at self-perceived competence (p=.000), physical appearance (p=.000), physical strength (p=.001) and self-confidence (p=.000). Therefore, according to the reached results, it can be concluded that, among the participants of this study, gender as well as sport practice have influence on the development of a positive physical self-concept.